Prinsip-Prinsip Ekonomi Dalam Budaya Tunjuk Ajar Melayu - Daharmi Astuti; Ag Maulana; Boy Syamsul Bakhri; Mona Fairuz Ramli (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2022)
ABSTRACT This paper is motivated by the lack of studies in Malay Economic system which rich cultural treasure, one of which is called Tunjuk Ajar. This term means teaching, advice, and rules in life for the Malays. One of the figures who wrote Tunjuk Ajar Melayu was a culturalist, Tenas Effendy. The research problem to be addressed is how the economic values in Malay teaching and learning are correlated with Islamic values. This paper hence explores Islamic principles in Malay community's economy and culture. The method used is library research with historical and philosophical approaches. The study found that there are eleven economic principles in the Tunjuk Ajar that are in line with the concept of Islamic Economics: trustworthy and accountable, fair and equitable, independent, anti-monopoly, self-confident and faithful, tolerant, balance between worldly and hereafter profit, alternate, broad-minded, social solidarity, and saving. This paper adds to literature on treasures of Malay culture, not only from a cultural perspective but also from an economic perspective as a work ethic for the Malay community. Keywords: Tunjuk Ajar, Malay, Economy, Islam. ABSTRAK Artikel ini ini dilatarbelakangi oleh minimnya kajian tentang perekonomian orang Melayu yang kaya akan khazanah, salah satunya disebut Tunjuk Ajar. Istilah ini berarti “pengajaran, nasihat serta aturan-aturan dalam berkehidupan bagi orang Melayu”. Salah satu tokoh yang menuliskan Tunjuk Ajar Melayu adalah budayawan Tenas Effendy. Permasalahan yang dibahas dalam artikel ini adalah bagaimana nilai-nilai ekonomi dalam Tunjuk Ajar Melayu berkorelasi dengan nilai-nilai Islam. Tulisan ini menggali prinsip-prinsip Islam dalam ekonomi dan budaya yang dimiliki oleh masyarakat Melayu dan menggali korelasi antara nilai-nilai ekonomi dalam Tunjuk Ajar Melayu dengan nilai-nilai Islam. Metode yang digunakan library research dengan pendekatan historis dan filosofis. Hasil pembahasan ditemukan bahwa terdapat sebelas prinsip ekonomi dalam Tunjuk Ajar Melayu dan memiliki hubungan simetris dan sejalan dengan konsep Ekonomi Islam yaitu: amanah dan menepati janji, adil dan merata, kemandirian, anti monopoli, percaya diri serta tawakkal, tenggang rasa, keseimbangan antara laba dunia dan akhirat, berpada-pada, berwawasan luas, kesetiakawanan sosial, hemat cermat dan pantang menyerah yang diterapkan dalam kehidupan orang Melayu. Tulisan ini menyorot khazanah budaya Melayu tidak hanya dari segi budaya, tetapi juga dari segi ekonomi dan membangun etos kerja masyarakat Melayu yang sesuai dengan syariat Islam. Kata kunci: Tunjuk Ajar, Melayu, ekonomi, Islam.